Effects of beam interruption time on tumor control probability in single-fractionated carbon-ion radiotherapy for non-small cell lung cancer. (1st May 2015) - Inaniwa, T; Kanematsu, N; Suzuki, M; Hawkins, R B
Abstract: Carbon-ion radiotherapy treatment plans are designed on the assumption that the beams are delivered instantaneously, irrespective of actual dose-delivery time structure in a treatment session. As the beam lines are fixed in the vertical and horizontal directions at our facility, beam delivery is interrupted in multi-field treatment due to the necessity of patient repositioning within the fields. Single-fractionated treatment for non-small cell lung cancer (NSCLC) is such a case, in which four treatment fields in multiple directions are delivered in one session with patient repositioning during the session. The purpose of this study was to investigate the effects of the period of dose delivery, including interruptions due to patient repositioning, on tumor control probability (TCP) of NSCLC. All clinical doses were weighted by relative biological effectiveness (RBE) evaluated for instantaneous irradiation. The rate equations defined in the microdosimetric kinetic model (MKM) for primary lesions induced in DNA were applied to the single-fractionated treatment of NSCLC. Treatment plans were made for an NSCLC case for various prescribed doses ranging from 25 to 50 Gy (RBE), on the assumption of instantaneous beam delivery. These plans were recalculated by varying the interruption time τ ranging from 0 to 120 min between the second and third fields for continuous irradiations of 3 min per field based on the MKM. The curative doses that would result in a TCP of 90% were deduced for the respective interruption times. The curative dose was 34.5 Gy (RBE) for instantaneous irradiation and 36.6 Gy (RBE), 39.2 Gy (RBE), 41.2 Gy (RBE), 43.3 Gy (RBE) and 44.4 Gy (RBE) for τ = 0 min, 15 min, 30 min, 60 min and 120 min, respectively. The realistic biological effectiveness of therapeutic carbon-ion beam decreased with increasing interruption time. These data suggest that the curative dose can increase by 20% or more compared to the planned dose if the interruption time extends to 30 min or longer. These effects should be considered in carbon-ion radiotherapy treatment planning if a longer dose-delivery procedure time is anticipated.